Reconstruction of Obligatory Bequest in the Perspective of the Objectives of Islamic Law: Contextualizing Islamic Law in a Case Study of The Secret Wife in Polygamous Marriage - Rusdi Rizki Lubis; Asmuni Asmuni; Tamyiz Mukarrom; Candra Boy Seroza; Muhammad Irfan (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2025)
The concept of obligatory bequest (wasiat wajibah) represents a significant development in the reform of Islamic family law in Indonesia. While normatively regulated in Article 209 of the Compilation of Islamic Law (KHI), which mandates obligatory bequests to adopted children and adoptive parents, recent jurisprudence and Supreme Court Circulars have broadened its application. Courts have extended obligatory bequests to include non-Muslim heirs, stepchildren, children born out of wedlock, and more recently, to sirri (unregistered) wives in polygamous marriages. This study employs a qualitative method with both normative-juridical and empirical-juridical approaches, using maqāṣid al-sharīʿah (the objectives of Islamic law) as the analytical framework. The key contribution of this research lies in its doctrinal and jurisprudential reconstruction of obligatory bequest to encompass sirri wives—a group previously excluded from formal inheritance rights. It argues that Religious Court judges may justifiably grant obligatory bequests to sirri wives under specific conditions: (1) the legally registered wife was aware of the sirri marriage yet chose not to report it; (2) the sirri wife demonstrably fulfilled her marital duties; and (3) the marriage lasted for more than five years and was characterized by harmony and mutual support. This study thus contributes to the ongoing reform of Islamic inheritance law by offering a more inclusive and justice-oriented interpretation aligned with contemporary social realities and maqāṣid al-sharīʿah